A parallel algorithm for solving strong separability problem on the basis of Fejer mappings - Ershova, A.V.; Sokolinsky, I.M. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2011)
An approach to solving the problem of separating two convex nonintersecting polyhedrons by the layer of maximum thickness is proposed. A parallel algorithm based on a method of using Fejer mappings is described. This algorithm admits an efficient implementation on the massively parallel multiprocessor systems. The results of computing experiments confirming the efficiency of the proposed approach are discussed. This work was supported by the Russian Foundation for Basic Research (project N 09-01-00546а).